Livelihoods in the Limpopo, The Challenge Program for Water and Food Project No. 1, Increased food security and income in the Limpopo basin: integrating crops, water and soil fertility management options and links to markets - Mgonja, MA; Waddington, S; Rollin, D.; Masenya, M (International Crops Research Institute for the Semi-Arid Tropics, 2006)
This document summarizes presentations and discussions of the workshop to launch the Challenge Program on Water and Food Project No. 1 for the Limpopo river basin in southern Africa. The project is funded through the CGIAR's Challenge Program for Water and Food. It aims to improve food security and farm incomes for smallholder farmers in the Limpopo basin, which covers parts of Botswana, Mozambique, South Africa and Zimbabwe.